Financial-Lending Stimulation of the Development of the Agro-Industrial Complex in Kazakhstan and in the Russian Federation - KUBAYEV, Kazila Erikenovich; BAISHOLANOVA, Karlygash Sovetovna; SEITOVA, Gulnara Toktarovna; TARASOVA, Alexandra; MISHCHENKO, Olga A. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
This paper examines a set of measures for enhancing the financial-lending mechanism of government regulation and support of the agro-industrial complex (AIC) as part of the implementation of the Government Program for the Development of the Agro-Industrial Complex in Kazakhstan for the Period 2017–2021 and Russia’s Government Program for the Development of Agriculture and Regulation of Markets for Agricultural Produce, Raw Materials, and Food for the Period 2013–2020. The authors have analyzed the volumes of investment and subsidies directed at carrying into effect a set of activities on stimulating investment activity in the AIC. The paper brings forward a set of ways to enhance the mechanism of funding agricultural entities for the purpose of boosting the efficiency of agricultural production in the country.